ANALYSIS OF CASSAVA AND BANANA CHIPS STARTUP DEVELOPMENT IN THE FRAMEWORK OF PKM PROGRAM WALIKUKUN VILLAGE BANTEN PROVINCE - Khaeruman Khaeruman; Hafidz Hanafiah (Yayasan Education and Social Center, 2021)
Every community everywhere, both in the village and in the city, will undoubtedly face a social dynamic that is so complex. From that dynamic then arises problems according to the conditions that envelop it. The problems will undoubtedly be tried to be solved by the community where the problem arises. Community service will not go well if it is not based on the spirit of research to help solve problems faced by the community. In this regard, the involvement of Bina Bangsa University through lecturers as researchers, facilitators and motivators. The position of society remains as the perpetrator and driver of change itself. Community Service is conducted for a month by applying health protocols through interviews and observations and literature studies with BMC (Business Model Canvas) or Canvas Business Model in solving problems. The study results found that umkm startup Kripik Singkong mentioned in the Canvas Business Model that there are nine things. MSMEs Kripik Singkong and Kripik Pisang can apply this approach to solve the problems faced by MSME startups